A new method for ecologists to estimate heterozygote excess and deficit for multi‐locus gene families - Gabe D. O'Reilly; Oliver Manlik; Sandra Vardeh; Jennifer Sinclair; Belinda Cannell; Zachary P. Lawler; William B. Sherwin (Ecology and Evolution)
Abstract The fixation index, FIS, has been a staple measure to detect selection, or departures from random mating in populations. However, current Next Generation Sequencing (NGS) cannot easily estimate FIS, in multi‐locus gene families that contain multiple loci having similar or identical arrays of variant sequences of ≥1 kilobase (kb), which differ at multiple positions. In these families, high‐quality short‐read NGS data typically identify variants, but not the genomic location, which is required to calculate FIS (based on locus‐specific observed and expected heterozygosity). Thus, to assess assortative mating, or selection on heterozygotes, from NGS of multi‐locus gene families, we need a method that does not require knowledge of which variants are alleles at which locus in the genome. We developed such a method. Like FIS, our novel measure, 1HIS, is based on the principle that positive assortative mating, or selection against heterozygotes, and some other processes reduce within‐individual variability relative to the population. We demonstrate high accuracy of 1HIS on a wide range of simulated scenarios and two datasets from natural populations of penguins and dolphins. 1HIS is important because multi‐locus gene families are often involved in assortative mating or selection on heterozygotes. 1HIS is particularly useful for multi‐locus gene families, such as toll‐like receptors, the major histocompatibility complex in animals, homeobox genes in fungi and self‐incompatibility genes in plants.